Education outside the classroom in Germany: An interdisciplinary multi-methods Study Protocol - Anna Brandmeier; Melissa Börner; Theres Mühlberg; Leonie Schulz; Lukas Kleinhenz; Theresia Endriß; Stephan Ellinger; Jan Schmid-Ellinger (PLoS ONE, 2026)
Background Schools are a central place in the lives of both children and teachers, with the potential to counteract current challenges such as a physical and emotional disconnection from nature, insufficient physical activity, and increased social isolation. Concepts like Education Outside the Classroom (EOtC) offer a variety of approaches and are already established in the curriculum in other countries, while in Germany EOtC is still in the early stages of implementation. Previous studies have focused on the effects of EOtC on students, with little attention paid to teachers, environmental perception, or behavioural analyses. This study aims to evaluate the impact of EOtC on teachers’ stress level, teachers’ well-being and physical activity, pupils’ cognitive performance, school-related well-being, basic psychological needs and classroom behaviour. In addition, this study investigates how the biodiversity of selected outside learning environments affects pupils’ and teachers’ nature connectedness, appreciation of nature and species knowledge. Methods This study protocol describes an exploratory, quasi-experimental, interdisciplinary study conducted in a total of 33 schools throughout Germany. Data collection will be carried out from September 2025 to November 2026. The first results of the data collection are expected in October 2026. It includes approximately 50 EOtC teachers, 50 non-EOtC teachers, 50 EOtC classes, and 18 non-EOtC classes with for intra- and interindividual comparisons. Data collection covers aspects from the fields of health, ecology, school pedagogy, and sociology and includes both pupils and teachers as target groups, as well as the various outdoor learning environments. For pupils and teachers, the study examines the effects of EOtC on nature connectedness, appreciation of nature, and plant and animal species knowledge. This is assessed twice per school year with questionnaires and compared to control classes within the same schools. In addition, for pupils, cognitive performance, measured by electroencephalography (EEG), school-related well-being, and basic psychological needs – both assessed via questionnaires – will be analysed. For teachers, stress levels, emotional well-being, and physical activity will be assessed using salivary cortisol samples, accelerometery, and questionnaires on both EOtC and regular teaching days, enabling intraindividual analyses. Moreover, teaching characteristics will be documented, and video-based analyses of social interactions between teachers, pupils, the outdoor learning environment, and teaching objects are conducted. Finally, biodiversity at the outdoor learning sites and their effects on the other study variables (e.g., nature connectedness, appreciation of nature, species knowledge and well-being of pupils and teachers) will be statistically analysed. Discussion This interdisciplinary study design provides a realistic analysis of the potential effects of EOtC on pupils, as well as teachers, while minimizing interference with the regular teaching process. A strength of this study is the consisted inclusion of teachers as a target group, as well as the ecological perspective and the use of innovative survey methods such as the recording of biodiversity, the video analysis of interactions and the analysis of lesson characteristics in the context of EOtC. This study will thus contribute to closing central research gaps in the German context and provide valuable insights for international EOtC research.